Experiential learning in high energy physics: a survey of students at the LHC. (9th January 2017) - Camporesi, Tiziano; Catalano, Gelsomina; Florio, Massimo; Giffoni, Francesco
Abstract: More than 36 000 students and post-docs will be involved until 2025 in research at the Large Hadron Collider (LHC) mainly through international collaborations. To what extent they value the skills acquired? Do students expect that their learning experience will have an impact on their professional future? By drawing from earlier literature on experiential learning, we have designed a survey of current and former students at LHC. To quantitatively measure the students' perceptions, we compare the salary expectations of current students with the assessment of those now employed in different jobs. Survey data are analysed by ordered logistic regression models, which allow multivariate statistical analyses with limited dependent variables. Results suggest that experiential learning at LHC positively correlates with both current and former students' salary expectations. Those already employed clearly confirm the expectations of current students. At least two not mutually exclusive explanations underlie the results. First, the training at LHC is perceived to provide students valuable skills, which in turn affect the salary expectations; secondly, the LHC research experience per se may act as signal in the labour market. Respondents put a price tag on their learning experience, a 'LHC salary premium' ranging from 5% to 12% compared with what they would have expected for their career without such an experience at CERN.